2017
DOI: 10.1016/j.spa.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Statistical inference for perturbed multiscale dynamical systems

Abstract: We study statistical inference for small-noise-perturbed multiscale dynamical systems. We prove consistency, asymptotic normality, and convergence of all scaled moments of an appropriatelyconstructed maximum likelihood estimator (MLE) for a parameter of interest, identifying precisely its limiting variance. We allow full dependence of coefficients on both slow and fast processes, which take values in the full Euclidean space; coefficients in the equation for the slow process need not be bounded and there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Meanwhile, it is shown also in [24] that direct application of the principle of maximum likelihood with discretely-sampled data via Euler-Maruyama approximation produces consistent estimates only if the data is first appropriately subsampled. Most closely related to the present work are [13,31], wherein the authors prove consistency and asymptotic normality of the continuous-data MLE for special cases of (1).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Meanwhile, it is shown also in [24] that direct application of the principle of maximum likelihood with discretely-sampled data via Euler-Maruyama approximation produces consistent estimates only if the data is first appropriately subsampled. Most closely related to the present work are [13,31], wherein the authors prove consistency and asymptotic normality of the continuous-data MLE for special cases of (1).…”
Section: Introductionmentioning
confidence: 76%
“…Given Theorem 1 and Lemma 6, the proof of Lemma 7 is similar to that of Lemma 10 in [13]; we omit the details.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where ν 0,Xt t (dy) is a probability measure supported on finitely many global minima of U (X t , ·) (see Theorem 1.3). If an additional assumption on the behaviour of U (x, ·) at its global minima is made then we show that ν 0,Xt t (dy) is time independent and given by a determinantal formula arising from In related works, Spiliopoulos in [Spi13,Spi14], Morse and Spiliopolous in [MS17], and Gailus and Spiliopoulous in [GS17] considered a class of coupled diffusions with multiple time scales in the full dependence setting. Contained therein, after suitable relabelling of the parameters and appropriate choice of coefficients, are results that will apply to (1)-(2) for specific b, ∇ y U and with s(ε) = ε α− 1 2 .…”
Section: Introductionmentioning
confidence: 88%
“…For simple models in molecular dynamics, the effect of model misspecification was studied in a series of papers [7,8,16,17,26,28,29] under the assumption of scale sep-aration. In particular, for Brownian particles moving in two-scale potentials it was shown that, when fitting data from the full dynamics to the homogenized equation, the maximum likelihood estimator (MLE) is asymptotically biased [29,Theorem 3.4].…”
Section: Literature Reviewmentioning
confidence: 99%